Study of variations in the branching pattern of thoracodorsal nerve - Bhosale, Santosh Manohar; Mallashetty, Nagaraj S. (International Journal of Research in Medical Sciences, 2017)
Background: Purpose of current study was to describe the variations in the origin of the thoracodorsal nerve of the posterior cord of brachial plexus and its distance of origin from mid-clavicular point in the South Indian population. These variations are important during surgical approaches to the axilla and upper arm, administration of anesthetic blocks, interpreting effects of nervous compressions and in repair of plexus injuries. The patterns of branching show population differences. Data from the South Indian population is scarce. Methods: Forty brachial plexuses from twenty formalin fixed cadavers were explored by gross dissection. Origin and order of branching of axillary nerve and its distance of origin from mid-clavicular point was recorded. Representative photographs were then taken using a digital camera (Sony Cybershot R, W200, 7.2 Megapixels). Results:In forty specimens studied, 72.5% of thoracodorsal nerves originated from posterior cord, which was predominant (75%) on the left side, 15% arose from axillary nerve which was observed in 20% of the right sided specimens and 12.5% had origin from the common trunk which was significant (15%) on the left side. In 32.5% of specimens, thoracodorsal nerve had origin at a distance of 4.1-4.5 cm, in 32.5% at a distance of 4.6-5.0 cm, in 17.5% at a distance of 5.1-5.5 cm, in 12.5% at a distance of 3.6-4.0 cm and in 5% at a distance of t more than 5.5 cm from mid-clavicular point. Conclusion: Majority of thoracodorsal nerves in studied population display a wide range of variations. Significant number of thoracodorsal nerve also takes origin from axillary nerve and from common trunk at various distances from a fixed point. Anesthesiologists administering local anesthetic blocks, clinicians interpreting effects of nerve injuries of the upper limb and surgeons operating in the axilla should be aware of these patterns to avoid inadvertent injury and this study provide the necessary insight into the branching pattern of the thoracodorsal nerve and its distance of origin. Further study of the origin of thoracodorsal nerve of posterior cord of brachial plexus and its distance of origin from mid-clavicular point is recommended.